Unsteady hydrodynamic forces acting on a robotic arm and its flow field during the crawl - Takagi, H.; Nakashima, M.; Ozaki, T.; Matsuuchi, K. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The importance of unsteady phenomena in human swimming has been emphasised in previous studies (Sanders 1999; Toussaint et al. 2002), hence we know that quasi-steady hydrodynamic theory is insufficient to describe the mechanisms by which humans propel themselves through water. To address such problems, computational fluid dynamics (CFD), including the effects of unsteady fluid flow, has been making a major contribution to understanding hydrodynamic phenomenon when the swimmer was moving actively either on the surface or underwater (Von Loebbecke et al. 2009; Dabnichki 2011). Particle image velocimetry (PIV) has also proven to be a powerful tool for measuring the actual flow fields around human swimmers. Based on PIV measurements, Matsuuchi et al. (2009) have reported that a pair of counter-rotating vortices might play an important role in generating unsteady fluid forces, and Hochstein and Blickhan (2011) have found that vortices generated in the region of strongly flexing joints are suitable to enhance propulsion; this process is known as vortex recapturing. Combining the results from CFD and PIV should help in visually and theoretically understanding complicated hydrodynamic mechanisms. However, actual experiment data, such as for forces and pressures, are also valuable for verifying CFD results and interpreting PIV images. Therefore, in a previous study, we conducted experiments in which we directly measured hydrodynamic forces, pressure distributions, and flow fields around a hand attached to a robotic arm (Takagi et al. 2013). In that work, simple 2D hand motions were the subject for study; nevertheless, a significant unsteady hydrodynamic phenomenon was observed that reveals the behavior of certain kinds of vortices play an essential role in generating substantial unsteady hydrodynamic forces. In this study, we used a robotic arm and PIV to clarify the mechanisms by which unsteady forces are generated during 3D crawl-stroke-motions. By analyzing the 3D motions, it is expected that actual propelling mechanisms can be elucidated and the findings will contribute to an improvement of swimmers' technique.